Exploring the Involvement of NLRP3 and IL-1β in Osteoarthritis of the Hand: Results from a Pilot Study - Antonella Fioravanti; Sara Tenti; Megan McAllister; Melody Chemaly; Amanda Eakin; Joseph McLaughlin; Anthony J. Bjourson; Elena Frati; Victoria McGilligan; Sara Cheleschi; David S. Gibson (Hindawi Limited, 2019)
Hand osteoarthritis (HOA) includes different subsets; a particular and uncommon form is erosive HOA (EHOA). Interleukin- (IL-) 1β plays a crucial role in the pathogenesis of osteoarthritis (OA); it is synthesized as an inactive precursor which requires the intervention of a cytosolic multiprotein complex, named inflammasome, for its activation. The aim of this study was to investigate the involvement of IL-1β and the NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome in patients with EHOA and nonerosive HOA (NEHOA) compared to healthy controls. In particular, we evaluated the gene expression of IL-1β and NLRP3, the serum levels of IL-1β, IL-6, IL-17, and tumor necrosis factor- (TNF-) α, and the protein levels of IL-1β and NLRP3. We also assessed the relationships between IL-1β and NLRP3 and clinical, laboratory, and radiological findings. Fifty-four patients with HOA (25 EHOA and 29 NEHOA) and 20 healthy subjects were included in the study. Peripheral blood mononuclear cell (PBMC) gene and protein expressions of IL-1β and NLRP3 were quantified by quantitative real-time PCR and western blot. IL-1β, IL-6, IL-17, and TNF-α serum levels were determined by ELISA. IL-1β gene expression was significantly reduced (p=0.0208) in EHOA compared to healthy controls. NLRP3 protein levels were significantly increased in the NEHOA group versus the control (p=0.0063) and EHOA groups (p=0.0038). IL-1β serum levels were not significantly different across the groups; IL-6, IL-17, and TNF-α were not detectable in any sample. IL-1β concentrations were negatively correlated with the Kellgren-Lawrence score in the whole population (r=−0.446; p=0.0008) and in NEHOA (r=−0.608; p=0.004), while IL-1β gene expression was positively correlated with the number of joint swellings in the EHOA group (r=0.512; p=0.011). Taken together, our results, showing poorly detectable IL-1β concentrations and minimal inflammasome activity in the PBMCs of HOA patients, suggest a low grade of systemic inflammation in HOA. This evidence does not preclude a possible involvement of these factors at the local level.